Women’s Language Features of an Ancient Chinese Female Warrior Disguised as a Male in “Mulan” - Elizabeth Sylvania Lie (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The main purpose of this study was to find out and explain the functions of women’s language features that are used by Mulan in the movie. This study applied qualitative and descriptive methods while the primary data were taken from the utterances said by the main character in the movie. The method that was used to collect the data was the documentation method through the note-taking technique. The data analysis was analyzed using the theory proposed by Lakoff in 1975, supported by the theory by Holmes in 2013. The result of this study showed that there are five out of ten features found in the character utterances: lexical hedges or fillers, super polite forms, hypercorrect grammar, emotional emphasis, and empty adjectives. The character mostly uses the women’s language features in her utterances as a hedging device rather than boosting device. She uses it as a symbol of her self-expression regarding her hesitation, politeness, and her emotions throughout the movie.